Articulating bodies : the narrative form of disability and illness in victorian fiction. - Hingston, Kylee-Anne (Representations (Liverpool, England), 2019)
Articulating Bodies shows how Victorian fiction's narrative form as well as narrative theme to negotiate how to categorize bodies, both constructing and questioning the boundary dividing normalcy from abnormality.